Global Differences in Online Shopping Behavior: Understanding Factors Leading to Trust. Issue 4 (1st October 2016) - Clemons, Eric K.; Wilson, Josh; Matt, Christian; Hess, Thomas; Ren, Fei; Jin, Fujie; Koh, Noi Sian
Abstract: Trust underlies much of the online shopping behavior. We compare trust in online shopping in four countries: (1) the United States, a mature online market; (2) Germany; (3) China, the fastest growing online market, where consumers are plagued by counterfeits, forgeries, and spoiled or defective items; and (4) Singapore. We performed laboratory experiments in all four countries. We used three experimental treatments: (1) no assurances; (2) promises of product quality and authenticity; and (3) promises backed up by third-party assurances. We examined subjects' perceived risk associated with different treatments across different vendor types. The impact of treatments and of vendor reputation on consumers' trust varied across countries in ways that we did not expect. In mature online markets like the United States, online shopping appears to be treated as just another form of shopping. In China, if an online vendor can establish a reputation for quality, consumers appear to treat those merchants much as Americans do their own favorite online vendors, despite problems with Chinese shopping more generally.